A review of previous studies on the Sri Lankan echinoid fauna, with an updated species list - Arachchige, Gayashan M.; Jayakody, Sevvandi; Mooi, Rich; Kroh, Andreas (Zootaxa, 2017)
A comprehensive review and analysis of the literature on echinoids from Sri Lankan waters were conducted to compile an annotated list that integrates the existing published data with original data from recent research. According to the published literature, 115 echinoid species and one subspecies have been reported from Sri Lanka to date. However, the current study revealed that only 66 echinoid species and one subspecies belonging to 20 families can be verified to occur in Sri Lankan waters. According to the present analysis, 49 species were excluded from the list due to uncertain records (16) or synonymy (33) with other taxa known from the region. Of the 66 species and one subspecies occurring in Sri Lankan waters, 11 were first described from type material collected from this region. Six of the type specimens are “regular” echinoids and five are Irregularia. Out of these 11, Araeosoma coriaceum indicum has been recorded only from and appears to be endemic to Sri Lankan waters. However, 34 species of Sri Lankan echinoids have not been recorded in the last 90 years. Echinoid species recorded from Sri Lankan waters represent 6.7% of the currently accepted species of extant echinoids and include representatives of 28% of the extant echinoid families. Forty-five percent (45%) of echinoids recorded from the Indian coast (113 species and subspecies) are present in Sri Lankan waters. The current study highlights the need for systematic revision of echinoid records in Sri Lanka through field surveys and reconciliation of discrepancies in the existing literature. Offshore sampling is also needed due to lack of recent information on local deep-sea echinoids.